Updating Experimental Models of Diabetic Cardiomyopathy - J. Fuentes-Antrás; B. Picatoste; A. Gómez-Hernández; J. Egido; J. Tuñón; Ó. Lorenzo (Journal of Diabetes Research)
Diabetic cardiomyopathy entails a serious cardiac dysfunction induced by alterations in structure and contractility of the myocardium. This pathology is initiated by changes in energy substrates and occurs in the absence of atherothrombosis, hypertension, or other cardiomyopathies. Inflammation, hypertrophy, fibrosis, steatosis, and apoptosis in the myocardium have been studied in numerous diabetic experimental models in animals, mostly rodents. Type I and type II diabetes were induced by genetic manipulation, pancreatic toxins, and fat and sweet diets, and animals recapitulate the main features of human diabetes and related cardiomyopathy. In this review we update and discuss the main experimental models of diabetic cardiomyopathy, analysing the associated metabolic, structural, and functional abnormalities, and including current tools for detection of these responses. Also, novel experimental models based on genetic modifications of specific related genes have been discussed. The study of specific pathways or factors responsible for cardiac failures may be useful to design new pharmacological strategies for diabetic patients.